Social Approbation Towards Women Empowerment : A Glimpse - Gulzar S Sanghera, Lenika Kashyap, Gagandeep Kaur and Manoj Sharma (Journal of Krishi Vigyan, 2015)
A woman’s contribution to the mankind has been widely recognized in every field of life. Days have been designated for her role in appreciation of motherhood-the divinity to the mankind, her recognition as a person, her quality to man, celebrating the girl child, protection of women in the society, happiness, joy and entertainment for women empowerment of rural women. Social approbation is must to execute various policies framed for empowerment of women. Using scientific information (women scientist Scheme) to improve the lives of women will help unravel the vast amount of untapped potential as it equips them with a scientific outlook and logical thinking ability which would greatly influence the mindset of the society